A case of transient epileptic amnesia with radiological localization. - Butler, C; Zeman, A (2008)
BACKGROUND: A 54-year-old man presented to a cognitive disorders clinic having experienced recurrent episodes of transient amnesia over a number of years. The attacks often occurred on waking, did not affect other cognitive abilities such as perception, language or judgment, and typically lasted about half an hour. The attacks were sometimes associated with olfactory hallucinations. Between amnestic episodes, the patient noticed a gradual deterioration in his recall of remote events, despite normal performance on standard memory tests. INVESTIGATIONS: Physical examination, laboratory tests, EEG, MRI brain scan, PET imaging, and neuropsychological assessment. DIAGNOSIS: Transient epileptic amnesia. MANAGEMENT: Anticonvulsant medication.